Pembangunan Sistem Inventory PT. Raja Roti Cemerlang Berbasis Web - Percikjernih Riak Telaga; Harfebi Fryonanda (UNIVERSITAS KALBIS, 2022)
Inventory is a stock of goods store for the purpose of future production or sales. The term inventory refers to all raw materials, parts, supplies, tools, process or finished products recorded in the books by an organisation and kept in its stocks, warehouse or plant for some period of time. This research was conducted to build a system that is applied to the warehouse of PT. Raja Roti Cemerlang. This research uses a prototype method by building a web-based inventory system. In the process of collecting data, researchers used interviews and direct observation to the warehouse admin. The result of the research is a web-based inventory system that can assist users in carrying out finished goods and raw materials in the warehouse.